2017
DOI: 10.1590/1678-4685-gmb-2017-0030
|View full text |Cite
|
Sign up to set email alerts
|

Multiple genes contribute to anhydrobiosis (tolerance to extreme desiccation) in the nematode Panagrolaimus superbus

Abstract: The molecular basis of anhydrobiosis, the state of suspended animation entered by some species during extreme desiccation, is still poorly understood despite a number of transcriptome and proteome studies. We therefore conducted functional screening by RNA interference (RNAi) for genes involved in anhydrobiosis in the holo-anhydrobiotic nematode Panagrolaimus superbus. A new method of survival analysis, based on staining, and proof-of-principle RNAi experiments confirmed a role for genes involved in oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 68 publications
(95 reference statements)
2
13
0
1
Order By: Relevance
“…In particular, Pratylenchus spp. can adopt a strategy known as anhydrobiosis that allows the juvenile and adult stages to survive periods without plant hosts or severe dry, cold, or hot conditions [27,28]. During anhydrobiosis, metabolism and life processes are slowed down, but Pratylenchus spp.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Pratylenchus spp. can adopt a strategy known as anhydrobiosis that allows the juvenile and adult stages to survive periods without plant hosts or severe dry, cold, or hot conditions [27,28]. During anhydrobiosis, metabolism and life processes are slowed down, but Pratylenchus spp.…”
Section: Introductionmentioning
confidence: 99%
“…4). The potential contribution of calcium signalings to anhydrobiosis was also suggested in tardigrades and nematodes 67,68 . In the anhydrobiotic tardigrade, Hypsibius dujardini, a calmodulin inhibitor (J-8) and a calcium release modulator (2-APB) reduced the survival rate after rehydration, but the inhibitors against CaN and CaMK had no effect on the anhydrobiotic ability.…”
Section: Discussionmentioning
confidence: 88%
“…Given that calmodulin regulates the gating of calcium ion channel in endoplasmic reticulum and mitochondrion as well as the signaling pathways 69,70 , the J-8 and 2-APB treatments may disrupt calcium storage in the organelles rather than calcium signalings, leading to malfunction of those intracellular organelles 71,72 . RNAi-based screening using the nematode Panagrolaimus superbus, showed that knockdown of “CAMK/CAMKL/MELK protein kinase” decreased the survival rate after rehydration 68 , whereas the contribution of CaN - NFAT pathway or CREB on the anhydrobiotic ability was not assessed. Our detailed experiments show that the CaM - CaN - NFAT pathway activation confers the tolerance to both trehalose incubation and desiccation on Pv11 cells, while the CaM - CaMK - CREB pathway activation gives only desiccation tolerance (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…However, such a sample requires strong precautions to minimize the possibility of contamination 23,38,42 . After rigorous filtering of possible contaminants as described above, we generated a 153. appears to be a common mechanism in anhydrobiosis, not one that is limited to tardigrades 43,44 . In addition, we identified several genes in stress signaling pathways, i.e., genes involved in stress signaling pathways.…”
Section: Discussionmentioning
confidence: 99%